Pengaruh Kompetensi Sumber Daya Manusia Dan Penerapan Standar Akuntansi Pemerintahan Terhadap Kualitas Laporan Keuangan Desa Sekecamatan Sukorejo Kabupaten Ponorogo - Awwalun Nashikhin, Saiful (UMSurabaya Publishing, 2024)
Regional government financial reports are very necessary for the public to know the accountability of regional governments. Financial reports are said to be quality if there are no such problems. In carrying out its activities, the village government must build and have a good internal control system, as a result, cases often occur such as: corruption, misuse of village finances, waste of budgets and poor quality of village government financial reports. One of them is a weak internal control system such as lack of quality human resources, lack of training for financial staff, lack of information technology and inadequate implementation of standards. Data collection was carried out using primary data in the form of a questionnaire. The sample processed in this research was 131 respondents who were distributed to village officials in the Sukorejo District, Ponorogo Regency. The data analysis method uses validity tests and reliability tests. Hypothesis testing uses multiple linear regression analysis. The results of this research show that human resource competency and the implementation of government accounting standards partially have a positive and significant effect on the quality of financial reports